Aligning Sharia-Based Empowerment with SDGs: Addressing Poverty and Inequality in Coastal Regions - Suryanto, Tulus; Utami, Pertiwi; Ahmad, Roslizawati (Economica: Jurnal Ekonomi Islam, 2024)
A significant portion of coastal communities in Indonesia continues to experience extreme poverty. Addressing poverty is a key priority of the Sustainable Development Goals (SDGs), yet achieving equality and social justice remains challenging due to various obstacles. This study employs a literature review to explore the relationship between the SDGs and efforts to achieve equality and social justice, focusing on approaches to alleviate extreme poverty in coastal communities through Sharia-based community empowerment. The first finding highlights that the SDGs can serve as a tool to secure equality and social justice for coastal communities. The second finding suggests that a Sharia entrepreneurship approach, emphasizing the potential of these communities, can be implemented through government support, Sharia banking, and Sharia social financial institutions. The study concludes that the SDGs play an important role in achieving equality and social justice, supported by Sharia-based community empowerment initiatives. These findings are intended to provide guidance for stakeholders in developing community-centered empowerment strategies. This requires not only focusing on funding programs and policies but also on enhancing the capacity of human resources, particularly in Islamic business ethics, technology, and institutional development.